2005
DOI: 10.1095/biolreprod.104.038216
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Gonadotropins and Their Receptors: II. Cloning and Characterization of Zebrafish Follicle-Stimulating Hormone and Luteinizing Hormone Subunits—Their Spatial-Temporal Expression Patterns and Receptor Specificity1

Abstract: Gonadotropins, follicle-stimulating hormone (FSH), and luteinizing hormone (LH) play critical roles in vertebrate reproduction. In the present study, we cloned and characterized zebrafish FSHbeta (fshb), LHbeta (lhb), and GTHalpha (cga) subunits. Compared with the molecules of other teleosts, the cysteine residues and potential glycosylation sites are fully conserved in zebrafish Lhb and Cga but not in Fshb, whose cysteines exhibit unique distribution. Interestingly, in addition to the pituitary, fshbeta, lhbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
136
0
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(164 citation statements)
references
References 99 publications
20
136
0
8
Order By: Relevance
“…For example, in mammals gpa expression precedes lhb and fshb expression in mouse (Japon et al, 1994) and human gonadotropes (Pope et al, 2006), which may explain the inability to detect lhb transcripts in the pituitary of zebrafish when gpa could be detected. In addition, the presence of two lhb genes in zebrafish (So et al, 2005) could lead to partially divergent function or tissue distribution, possibly explaining the proposed earlier onset of lhb gene expression relative to medaka.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in mammals gpa expression precedes lhb and fshb expression in mouse (Japon et al, 1994) and human gonadotropes (Pope et al, 2006), which may explain the inability to detect lhb transcripts in the pituitary of zebrafish when gpa could be detected. In addition, the presence of two lhb genes in zebrafish (So et al, 2005) could lead to partially divergent function or tissue distribution, possibly explaining the proposed earlier onset of lhb gene expression relative to medaka.…”
Section: Discussionmentioning
confidence: 99%
“…Upon release, LH and FSH bind to their specific receptors, LHR and FSHR, in the gonads, stimulating steroidogenesis and gametogenesis. Gonadotropin receptors, however, are expressed in multiple tissues also outside the b-p-g axis (Kumar et al, 2001;Vischer and Bogerd, 2003;Wong and Van Eenennaam, 2004;So et al, 2005;Rocha et al, 2007;Mittelholzer et al, 2009), suggesting LH and FSH could be involved in many physiological processes, although nonreproductive functions are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Not only does receptor localization differ, but cross-reactivity has also been described in binding assays with purified fish gonadotropins (Yan et al 1992) and in functional studies using mammalian cell lines expressing fish receptors separately. In African catfish (Bogerd et al 2001, zebrafish (So et al 2005), and Atlantic salmon (Andersson et al 2009), a promiscuous activation of Fsh receptors has been reported using high Lh concentrations. However, in two salmonid species, amago salmon and rainbow trout, only Fsh was able to activate Fshr (Oba et al 1999, Sambroni et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Nica et al (2004) cloned a zebrafish homologue of the gsu and found two distinct populations of cells; those that coexpressed pit1 (presumptive thyrotrophs) and those that did not (presumptive gonadotrophs). Most recently, the D. rerio genes for the gonadotrophins have been cloned (So et al 2005). Two LH isoforms (lh 1 and lh 2), fsh and GTH sequences were cloned, and their distribution was restricted to the pituitary, testis and ovaries.…”
Section: The Pituitarymentioning
confidence: 99%
“…Two LH isoforms (lh 1 and lh 2), fsh and GTH sequences were cloned, and their distribution was restricted to the pituitary, testis and ovaries. Sequence homology of LH and GSU with other fish species is reasonably high (70%), but less conserved for FSH (37-64%) (So et al 2005). In mammals, one of the key transcription factors responsible for the differentiation of gonadotroph lineage cells is steroidogenic factor-1 (SF-1), an ftz-f1 homologue.…”
Section: The Pituitarymentioning
confidence: 99%